Urban sprawl and public health : designing, planning, and building for healthy communities - Frumkin, Howard (Island Press, 2004)
"In Urban Sprawl and Public Health, three of the nation's leading public health and urban planning experts take a comprehensive look at the interface of urban planning, architecture, transportation, community design, and public health. They summarize the evidence linking adverse health outcomes with sprawling development, and outline the complex challenges of developing policy that promotes and protects public health. This book is essential reading for anyone concerned with issues of public health, urban planning, transportation, architecture, or the environment."--Jacket